Implikasi Bayang IstiwaaTerhadap Penentuan Awal Waktu Sholat - Abdulloh Hasan (Jurnal Penelitian Agama, 2021)
The formulation of prayer times is based on the apparent daily circulation of the Sun by determining when the Sun occupies a certain position. One of these positions when the Sun is perpendicular to the position of the observer is called the Solar Culmination Time or called istiwa. Time istiwa defined as the starting point of the reckoning the beginning of prayer time with a time angle value equal to zero. One of the phenomena in istiwa’ is the shadow of istiwa which is used as a guide in making sundials. The phenomena of the 'shadows' has many variants depending on the latitude of the place and the declination of the Sun. The number of variants of changes in the condition of the idols shadow becomes an interesting part to be studied and researched, especially the position of the idols time as the starpoint in the initial reckoning of prayer time. In addition, the implication of the shadow istiwa phenomenon is closely related to the beginning of Zuhr and Asr, which use the sun's shadow in their calculations. This paper will examine the implications of istiwa shadows on the initial determination of prayer times which will be more focused on changes in the phenomenon of istiwa'i shadows to variations in latitude and sun declination. The research method uses qualitative methods with an astronomical approach. The data obtained were processed using geometric techniques to obtain data variants. The results of data processing were analyzed with descriptive comparisons to get a more comprehensive picture. The results of the study show that with changes in the variation in the value of the latitude and declination of the Sun, a change in the phenomenon of the length of the images' image is obtained as follows: Without a shadow; b. The image does not exceed the length of the object; c. The image 'is equal to the object's length; d. Istiwa length 'is longer than the object length; e. Dark. The implication is in the formulation of Zuhr and Asr prayer times which refer to the length of the idols shadows experiencing problems. Especially areas with latitude > 45° degrees when declination is negative and latitude> -45° when declination is positive.